The effects of a large‐scale wind farm on breeding season survival of female mallards and blue‐winged teal in the Prairie Pothole Region. Issue 7 (12th August 2013) - Gue, C. Tanner; Walker, Johann A.; Mehl, Katherine R.; Gleason, Jeffrey S.; Stephens, Scott E.; Loesch, Charles R.; Reynolds, Ronald E.; Goodwin, Brett J.
ABSTRACT The wetlands and grasslands of the Prairie Pothole Region (PPR) make it the most productive breeding habitat for North American ducks. The growth rate of mallard (Anas platyrhynchos) populations is sensitive to changes in survival of adult females during the breeding season. Much of the PPR is suitable for large‐scale wind‐energy development and collisions of breeding females with wind turbines may be a novel source of mortality in this area. We assessed the effects of wind energy on breeding female mallard and blue‐winged teal (A. discors) survival by monitoring 77 radio‐marked mallards and 88 blue‐winged teal during the 2009 and 2010 breeding seasons at the Tatanka Wind Farm (TWF) near Kulm, North Dakota. During the same period, we monitored 70 female mallards and 75 blue‐winged teal at an adjacent reference site without wind turbines (REF). We used an information‐theoretic approach to investigate relationships between female survival and site (TWF vs. REF), year (2009 vs. 2010), and date. Collision mortalities were rare. Only 1 radio‐marked female mallard and no blue‐winged teal collided with wind turbines. Most mortalities were caused by predators (78.3%; 36/46), irrespective of species and site. For mallards, the best‐approximating model indicated that breeding season survival was 1) lowest when a high proportion of radio‐marked females were incubating, and 2) dependent on year and site such that expected survival (<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg37dt36h7" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />Sˆ</alternatives>) in 2009 was higher at TWF (<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg37dt36t6" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />Sˆ</alternatives> = 0.90, 85% CI = 0.79–0.98) than at REF (<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg37dt36sn" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />Sˆ</alternatives> = 0.83, 85% CI = 0.68–0.95), but expected survival in 2010 was lower at TWF (<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg37dt36p0" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />Sˆ</alternatives> = 0.62, 85% CI = 0.46–0.79) than at REF (<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg37dt36nf" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />Sˆ</alternatives> = 0.84, 85% CI = 0.72–0.94). For blue‐winged teal, the constant model was the best‐approximating model and indicated that expected female survival was 0.75 (85% CI = 0.69–0.82). The most competitive model for blue‐winged teal that included the effect of wind turbines indicated that expected survival at TWF (<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg37dt36xv" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />Sˆ</alternatives> = 0.71, 85% CI = 0.62–0.79) was lower than survival at REF (<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg37dt370g" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />Sˆ</alternatives> = 0.81, 85% CI = 0.73–0.89). The limited number of collisions observed for female mallards and blue‐winged teal nesting at TWF suggests that wind turbines had no direct effect on female survival. Thus, conservation strategies that include protection of wetland and grassland habitat in wind‐developed landscapes will most likely not cause a direct reduction in survival of breeding females due to collisions with wind turbines. © 2013 The Wildlife Society.